The effect of volume fraction of WC particles on wear behavior of in-situ WC/Fe composites by spark plasma sintering. (December 2017) - Zhang, Zhanzhan; Chen, Yunbo; Zuo, Lingli; Zhang, Yang; Qi, Yesi; Gao, Kewei
Abstract: Tungsten carbide (WC) particles have been in-situ synthesized through the reaction between tungsten particles and carbide particles by spark plasma sintering (SPS). The composites with different WC content were comparatively observed by the techniques of scanning electron microscopy (SEM), high-resolution transmission electron microscope (HRTEM), X-ray diffraction, hardness and pin-to-disc abrasive wear test. The results showed that the formed WC particles were homogenously distributed in the iron matrix with the size of smaller than 25 μm. Additionally, with the increasing of the WC content, the hardness of composites, the microhardness of matrix and the wear resistance increased, but there was no change significantly between 32 vol% WC/Fe composites and 42 vol% WC/Fe composites. The composites possessed excellent wear resistance comparing the specific wear rate determined in the present work to the martensitic wear-resistant steel under the load of 80 N after a sliding distance of 950 m. The specific wear rate of the martensitic wear-resistant steel was a factor of 24 and 48 times higher than WC/Fe composites, when the content of WC was 32 vol% and 42 vol% in WC/Fe composites, respectively. The main wear mechanism was synthetic of abrasion wear and oxidation wear. The wear performance of 32 vol% WC/Fe composites didn't appear to be much different from 42 vol% WC/Fe composites, due to the WC particles in the 42 vol% composites produced stress concentration easily, which could ultimately induce the creak initiation around WC particles in the subsurface (near wear surface) and propagation to wear surface promoting the breakup of surface film. Highlights: The composites with different WC content are fabricated by spark plasma sintering (SPS). The composites have the same wear resistance, when the contents of WC are 42 vol% and 32 vol%. The Fe3 W3 C phase between WC and matrix is determined by SEM-EDS, XRD and HRTEM. The orientation between the Fe3 W3 C and Fe3 C is (211)Fe3W3C //(100)Fe3C and [ 1 − 57]Fe3W3C //[00 1 − ]Fe3C .